Assessment of antioxidant activity, lipid profile, general biochemical and immune system responses of Wistar rats fed with dairy dessert containing Lactobacillus acidophilus La-5. (December 2016) - Moura, C.S.; Lollo, P.C.B.; Morato, P.N.; Esmerino, E.A.; Margalho, L.P.; Santos-Junior, V.A.; Coimbra, P.T.; Cappato, L.P.; Silva, M.C.; Garcia-Gomes, A.S.; Granato, D.; Bolini, H.M. A.; et al.
Abstract: The viability and survival of Lactobacillus acidophilus La5 under in vitro simulated gastrointestinal in probiotic dairy dessert was assessed. In addition, the effects of regular consumption of the dessert (5 g/day) on the lipid profile, immune system, and antioxidant/biochemical status of Wistar rats were also evaluated after 2 weeks of treatment. Adequate counts of L . acidophilus La-5 were observed regards the viability and gastrointestinal conditions. The probiotic dairy dessert was efficient in reducing the LDL-cholesterol, triacylglycerol and increased the HDL-cholesterol in serum. Aspartate amino transferase, alanine aminotransferase, total protein, albumin, heat shock proteins, immune system responses, and blood-cells counts (monocyte, lymphocyte, neutrophil and leucocyte) were not affected ( p  > 0.05) after 15 days of treatment. Overall, the probiotic dairy dessert may be a viable alternative to enhance the blood lipid profile and could be used to improve the antioxidant defenses. Graphical abstract: Highlights: Probiotic dairy dessert consumed along 15 days by Wistar Rats Viable probiotic count, survival in gastrointestinal condition and DPPH inhibition Improvement of plasma lipid profile parameters and improvement in markers of antioxidant defenses Any effect on the insulin metabolism and parameters of the immune system